Teachers’ Professional Development Courses to Ensure Quality Education - Brikmane, Karīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The focussed professional development of teachers ensures the quality of modern education. In the context of life-long education, each teacher has to develop their professional and personal competence, to ensure the development of general and professional skills and for teachers to be able to face new challenges and undertake their tasks in non-traditional, but well argued ways, because education strengthens intuition, confidence and the ability to knowingly transform acquired experience into innovation. The issue in the research establishes the contradictions seen within society between the goals set in education and their implementation in the teaching process. Attention has been focussed in this research on the current national situation in the professional development of teachers, gathering information on what is offered and researching the improvements needed for a modern adult learning process. The importance of the research was established by the need for changes in general education and the implementation of sustainable development principles. The main strategic principles, the observation of which could significantly increase the possibility of development are prescribed by the “Sustainable Development Strategy of Latvia until 2030”. They are – innovation, tolerance, co-operation and participation, which should also be included in the content of teachers’ professional development courses, in this way directly influencing the improvement of the quality of education as well.